Optimalisasi Proses Perakitan Pesawat Tanpa Awak dengan Metoda Critical Path Methods (CPM) - Dendi Adi Saputra M; Eka Satria; Gusman Arif Pandy (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2016)
The manufacturing of Unmanned Aerial Vehicles (UAV) requires a design process that involves the design of aircraft’s components such as fuselage, wing, horizontal stabilizer, vertical stabilizer, ailerons, elevators, tail, and wing. The process takes a long time. Therefore, the distribution of structural works based on their characteristics and classifications by considering their design attributes and manufacturing processes is required. This research aims to find the optimal time and critical path of the assembly process of an UAV based on product work breakdown structure (PWBS) and critical path method (CPM). The result reveals that the optimal assembly time is 139 minutes. Finally, the application of product-oriented structural work distribution and the optimization of the assembly activities involved in the critical path successfully minimize the duration of the assembly process.